Application and progress of new technologies and new materials in the treatment of pathological scar - Liu, Yining; Wang, Sisi; Yang, Fan; Wang, Xuepeng; Zhang, Jierui; Han, Xinkun; Zhang, Xipeng; Wang, Zhiguo (Frontiers in Chemistry, 2024)
Pathological scars (PS), including hypertrophic scars (HTS) and keloids, are a common complication of poor wound healing that significantly affects patients’ quality of life. Currently, there are several treatment options for PS, including surgery, drug therapy, radiation therapy, and biological therapy. However, these treatments still face major challenges such as low efficacy, high side effects, and a high risk of recurrence. Therefore, the search for safer and more effective treatments is particularly urgent. New materials often have less immune rejection, good histocompatibility, and can reduce secondary damage during treatment. New technology can also reduce the side effects of traditional treatments and the recurrence rate after treatment. Furthermore, derivative products of new materials and biomaterials can improve the therapeutic effect of new technologies on PS. Therefore, new technologies and innovative materials are considered better options for enhancing PS. This review concentrates on the use of two emerging technologies, microneedle (MN) and photodynamic therapy (PDT), and two novel materials, photosensitizers and exosomes (Exos), in the treatment of PS.